Two new species of Cuspidevia Jäch & Boukal, 1995 from China (Coleoptera: Elmidae) - Bian, Dongju; Ji, Lanzhu (Zootaxa, 2010)
Two new species of the genus Cuspidevia Jäch & Boukal, 1995 (Macronychini) are reported from Jiangxi Province, China: Cuspidevia brevis sp. nov., Cuspidevia jaechi sp. nov. Descriptions, diagnoses, illustrations and a key to Cuspidevia are given.